IMPLEMENTASI BUDAYA ORGANISASI, KECERDASAN EMOSIONAL DAN KEPRIBADIAN GURU DALAM PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH DASAR NEGERI PINANG 6 KOTA TANGERANG TAHUN 2025 - Niar Telaumbanua, Selvin; Sri Utaminingsih; Nuryati Djihadah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe and analyze the implementation of organizational culture, emotional intelligence, and teacher personality in improving the quality of education at SD Negeri Pinang 6, South Tangerang, in 2025. The background of this study is based on the importance of improving the quality of education, which is not only determined by curriculum and infrastructure aspects, but also by internal school factors, particularly organizational culture, emotional intelligence, and teacher personality as the main actors in the learning process. This study employed a qualitative approach with a descriptive research type and a case study method. Data collection techniques were carried out through in-depth interviews, participatory observation, and documentation studies. Research informants were determined purposively, including school supervisors, the principal, and teachers at SD Negeri Pinang 6. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing, while data validity was tested using source and technique triangulation.